Implementasi Kebijakan Pengelolaan Aset Tanah Menggunakan Aplikasi Simda Bmd Pada Badan Pengelola Keuangan Dan Aset Daerah Kota Sorong Provinsi Papua Barat - Hatumessen, Calvin Emerald; Effendy, Khasan; Rowa, Hyronimus (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
This research is entitled Policy Implementation of Lands Asset Management Used SIMDA BMD in the Financial Management Agency and Regional Assets of Sorong City, West Papua Province. The background of this research is due to the problem of managing asset in this case lands asset that frequently happen throughout all government instance in Indonesia. The quality of property organizer in managing regional property that are still not good is a further problem, as well as hardware and software factors in a few of Local Goverment Working Unit which is inadequate to use this Application (SIMDA BMD). The research methods in this study is qualitative method with an inductive approach. The Theory used is Grindel 1980:2 which state that ““the succesful implementation of public policy is influenced by two fundamental variabels that content of policy and context of implementation”. This means the success rate of implementing a policy is cause by two variable i.e the content of the policy and the implementation environment. The method of data collection is done by indirect observation, documentation, and interviews. The data analysis technique using SWOT analysis and Litmus Tests. The results of the study show that the Lands Asset Management Used SIMDA BMD In The Financial Management Agency And Regional Assets Of Sorong City, West Papua Province is still not running well and not able to resolve the problems of regional property management in Sorong City. This is based on the results of analysis and research which has been done by researchers, such as the existence of inadequate hardware facilities in course of running SIMDA BMD software, and the low quality of operators that have not been maximized in implementing this policy. The action that can be done by Sorong City Government are optimizing human resources which is available in Sorong City especially those who work in Government instance.